Occupational noise exposure and hypertension: a case-control study - Wang, Feixia; Song, Xianping; Li, Fenglei; Bai, Ying; Han, Lei; Zhang, Hengdong; Zhang, Feng; Luo, Xiaoming; Shen, Huanxi; Zhu, Baoli (Journal of Public Health and Emergency; Vol 2 (December 2018): Journal of Public Health and Emergency, 2018)
Background: Occupational noise exposure in the workplace is a significant health problem and hypertension is a widespread chronic disease. This study aimed to investigate whether occupational noise exposure is associated with hypertension in a Chinese population. Methods: A total of 286 hypertensive workers and 630 normotensive workers were enrolled and analyzed in a case-control study. Results: We revealed that workers exposed to noise can increase the risk of hypertension (adjusted OR 1.52, 95% CI: 1.11–2.08). This effect was more pronounced in ever smoking group (adjusted OR 2.54, 95% CI: 1.16–5.53). When noise exposure combined with never drinking status, it can reduce the risk of hypertension (adjusted OR 1.48, less than 1.52). Conclusions: Our results provide a clue that occupational noise exposure may increase the risk of hypertension in a Chinese population.